The dark side of nature conventions: A call to end anthropogenic wildlife destruction - Sollund, Ragnhild Aslaug (Criminology & criminal justice, 2025)
The world is experiencing an anthropogenic nature crisis, with global warming and catastrophes, for example, wildfires and flooding, causing destruction of living conditions and habitat both for human and nonhuman species. According to WWF’s last living planet index, one million species are risking extinction, leading to a need for a criminology that addresses the multifarious reasons for this situation, which to large degree is lacking. In this article, I apply perspectives from Green Criminology, Environmental Restorative Justice and Species Restorative Justice to argue for the necessity of these to address species loss and animal abuse caused by wildlife trade and hunting. The implementation of two prominent nature conservation conventions, CITES and the Bern convention, are central in the discussion, with Norway as the case, through which it is shown that these fail to provide endangered wildlife with protection.